Síndromes geriátricas e doenças crônicas: repercussões na capacidade funcional de pessoas idosas - Onófrio, Luisiana Fillipin (2023)
Geriatric syndromes and chronic non-communicable diseases (NCDs) can be considered a major public health problem, due to their great impact on quality of life and because they generate unfavorable effects on the functional capacity of the elderly. This research aims to evaluate the association between geriatric syndromes and the most prevalent chronic diseases and identify their repercussions on the functional capacity of elderly people treated in a geriatric outpatient clinic of a tertiary care hospital. The study is characterized as observational with cross-sectional follow-up and a quantitative approach. Data collection was carried out from electronic medical records via the Management Application for University Hospitals (AGHU), of elderly people of both sexes aged 60 or over, from March 2021 to March 2022. The data collected included the clinical and sociodemographic profile of the elderly, geriatric syndromes, and the Katz, Lawton, and Brody scales referring to functional capacity. This research is part of a larger project, entitled “Risk factors for the development of frailty in the elderly” and has CAAE number 61040222.5.0000.5346, and CEP number 5.572.399. The data were processed using the Statistics Package for the Social Sciences version 22.0. Association analyses were performed using the Chi-square test when the frequency in the contingency tables was greater than 5; otherwise, Fischer's exact test was used. For all statistical analyses, the significance level of p<0.05 was used as a reference. The research sample consists of medical records of 115 patients treated at the geriatric outpatient clinic. Regarding the sociodemographic profile, the sample was mostly composed of females, with a more prevalent age group of 80 years or more and low education. The most prevalent group of NCDs was cardiovascular, the majority were independent in basic activities of daily living (BADL) and in Instrumental activities of daily living (IADL) they had some degree of dependence to perform the activities. There was a statistical association between cardiovascular diseases and functional capacity and between all geriatric syndromes and BADL. There was no statistical significance related to IADL family insufficiency and communicative incapacity. The results of this research highlight that the geriatric syndrome with the highest incidence was postural instability. Furthermore, cardiovascular diseases were associated with functional capacity in both BADL and IADL. The high incidence of geriatric syndromes is a significant factor that negatively impacts the functional capacity of the elderly, generating a reduction in quality of life and increased morbidity in the elderly, and is generally not routinely screened or identified in most healthcare settings.